The effectiveness of the role of those involved in real estate promotion in protecting the real estate consumer - benfrid, hasnia; karima, krim (The journal of Teacher Researcher of Legal and political Studies, 2025)
The need for housing is an urgent necessity in the lives of individuals. That is why the legislator devoted the real estate activity related to housing to the term real estate promotion whose primary goal is to provide housing, and because this need is related to the field of construction and urbanization, its importance increases more and more since this field is one of the most difficult filds and one of the most complex, due to the multiplicity of stages And the procedures required for the completion of housing projects on the one hand, and for the large number of people involved in the completion of housing projects on the other hand, it was the duty of the legislator to control and regulate all stages and procedures, as well as the people and bodies active in this field